Celično zdravljenje s tolerogenimi dendritičnimi celicami - vzročno zdravljenje avtoimunskih bolezni - Švajger, Urban (Zdravniški vestnik, 2013)
Background: Dendritic cells (DCs) are considered as primary carriers of antigenic (Ag) information in the human body. This information is later presented to Ag-specific T lymphocytes in various ways that can be either immunostimulating or immunosuppressive. The latter depends on the activation status of DCs, in which way the DCs display extreme plasticity in terms of their function. Tolerogenic DCs, which are characterized by extensive immunosuppressive properties, can induce the generation of regulatory T lymphocytes or cause T-cell anergy. In the last two decades, considerable evidence has accumulated using animal models, which points to safety and efficacy of DC application in terms of treating immune-mediated diseases. Immun therapy using DCs is nowadays becoming a clinical reality. At present, a clinical study using autologous DCs derived from human monocytes and treated ex vivo to induce their immunosuppressive potential, with the aim to treat autoimmune type 1 diabetes, is registered within NIH (National Institutes of Health). Conclusion: The review discusses the characteristics of DCs, suitable for use in cellular therapy of autoimmune diseases, their role in such therapies and the way in which such cells can be generated in the laboratory. Therapy of autoimmune diseases using tolerogenic DCs represents an outstanding potential, however the major obstacles lay in the way of proper preparation of cellular products, where all procedures should follow the strict demands of good manufacturing practice (GMP).
Keywords: avtoimunske bolezni; dendritične celice; limfociti T; therapy; tolerogene dendritične celice; zdravljenje